Experimental study of bottom feed updraft gasifier - Pedroso, Daniel Travieso; Machín, Einara Blanco [UNESP]; Silveira, Jose Luz [UNESP]; Nemoto, Yasuyuki (Elsevier, 2013)
The updraft biomass gasifiers currently available produce a gas with high tar content. For almost all downstream applications a substantial reduction of the tar concentration is required. The gravimetric tar concentration behavior in producer gas, obtained at a modified updraft fixed bed gasifier, was studied. The feedstock feeding system was modified respect to the traditional updraft gasification design in order to decrease the tar concentration in the producer gas; the material is feeding continuously through a conduit in the base of the reactor over the grate. The caloric power of the syngas obtained was slightly lower than the typical value for this type of reactor and the highest efficiency obtained for the woodchip gasification was 77%. The highest tar concentration obtained during the experiments was 1652.7 mg N m-3 during the first our of experiments, comparable with the smaller value reported for the updraft reactors, this value is reduced significantly after the stabilization of the gasification process in the reactor. The smaller value obtained was 21 mg N m-3. © 2013 Elsevier Ltd.
Keywords: Biomass; Gasifier; Gravimetric tar; Renewable energy; Updraft; Downstream applications; Experimental studies; Feeding system; Fixed bed; Gasification process; Gasifiers; Producer gas; Renewable energies; Substantial reduction; Syn-gas; Tar concentration; Typical values; Updraft gasifier; Wood chip; Experiments; Gasification; Synthesis gas; Tar; biomass power; concentration (composition); energy efficiency; energy resource; experimental study; gravimetry; renewable resource; tar